Traditional Malay black ink: An analysis of its recipes and characteristics - Abdul Razak, Rajabi; Barkeshli, Mandana; Othman, Raihan (American Scientific Publisher, 2017)
Historically, the use and produce of Malay traditional ink were closely associated with the palaces and pondoks (Islamic religious school) where the early Malay manuscripts were traced. These Malay manuscripts can be traced dated back to the 16th century and the fact that those manuscripts have survived until today proves the durability and permanency of the traditional ink. Unfortunately, the documentation and description of such an indigenous ink making are scarce from the literature. Therefore, this work is dedicated to uncovering the legacy of Malay traditional ink recipe through several approaches, namely, analyse the recipe through historical literature and inspecting the characteristics of ink’s and its behaviour on existing early manuscript through microscopic analysis. The black ink was produced traditionally using natural resources that were available within a particular locality and applied on papers from foreign origin, either occidental or oriental. Ingredients used are varied which consists three important elements; colouring agent, adhesive and additives. The colouring agent determines the black ink’s pigment. As for the adhesive, its function is to ensure that the ink adheres well to the paper fibre, provide fluidity to the ink flow and improve the permanency and durability of the ink. Finally, the additives were often added to complement the roles of additives. Besides, they also serve to neutralize the odour of the solution and to shorten the ink drying time. The Malay manuscripts were examined under microscopic analyses revealed the characteristic qualities that prove the stability and permenancy of this traditional ink have prolonged the age of the manuscripts.